Problemy kupców angielskich handlujących z państwami nadbałtyckimi w latach sześćdziesiątych i siedemdziesiątych XVII wieku w świetle listów Francisa Sandersona - Krysztopa-Czupryńska, Barbara (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The 1660’s and 1670’s were an extremely difficult time for English merchants trading with the Baltic states. In the years 1665–1667 and 1672–1679, wars were fought in which countries lying on the Baltic Sea were involved. At that time, issues related to war conflicts and the problems arising from them dominated in the letters Sanderson sent to London. Another issue, which came to the fore in this period in relation to the English trade in the Baltic Sea, was the rivalry between the British and the Dutch. It took place on various levels – military, economic, and propaganda. While English merchants encountered various kinds of problems in Ducal Prussia. On the other hand, the situation of English merchants in Gdańsk was relatively good.